Comparing the performance of 12S mitochondrial primers for fish environmental DNA across ecosystems. Issue 6 (6th July 2021) - Polanco F., Andrea; Richards, Eilísh; Flück, Benjamin; Valentini, Alice; Altermatt, Florian; Brosse, Sébastien; Walser, Jean‐Claude; Eme, David; Marques, Virginie; Manel, Stéphanie; Albouy, Camille; Dejean, Tony; et al.
Abstract: Through the development of environmental DNA (eDNA) metabarcoding, in situ monitoring of organisms is becoming easier and promises a revolution in our approaches to detect changes in biodiversity over space and time. A cornerstone of eDNA approach is the development of primer pairs that allow amplifying the DNA of specific taxonomic groups, which is then used to link the DNA sequence to taxonomic identification. Here, we propose a framework for comparing primer pairs regarding (a) their capacity to bind and amplify a broad coverage of species within the target clade using in silico PCR, (b) their capacity to not only discriminate between species but also genera or families, and (c) their in situ specificity and efficiency across a variety of environments. As a case study, we focus on two mitochondrial 12S primer pairs, MiFish‐U and teleo, which were designed to amplify fishes. We found that the performance of in silico PCRs were high for both primer pairs, but teleo amplified more genera across Actinopterygii, Chondrichthyes, and Petromyzontomorphi than MiFish‐U. In contrast, the discriminatory power for species, genera, and families were higher for MiFish‐U than teleo, likely associated with the greater length of the amplified DNA fragments. The evaluation of their in situ efficiency showed a higher recovered species richness of teleo compared to MiFish‐U in tropical and temperate freshwater environments, but that generally both teleo and MiFish‐U primers pairs perform well to monitor fish species. Since more species were detected when used together, those primer pairs are best used in combination to increase the ability of species detection. Abstract : We propose a framework for comparing the performance of primer pairs, which we applied to the comparison of two fish eDNA primer pairs, teleo and MiFish‐U. We showed how those primer pairs could be best used together to increase diversity coverage of eDNA studies.